Stress, Burnout and Study-Related Behavior in University Students: A Cross-Sectional Cohort Analysis Before, During, and After the COVID-19 Pandemic - Verena Dresen; Siegmund Staggl; Laura Fischer-Jbali; Markus Canazei; Elisabeth Weiss (Brain Sciences, 2025)
Background/Objectives: The COVID-19 pandemic intensified stress among students, though its impact on burnout symptoms remains mixed. Previous research emphasized examining both study-related behavior such as academic engagement and burnout for a fuller understanding of students’ well-being in the wake of the COVID-19 pandemic. Methods: In this cross-sectional study we examined stress, burnout, study-related behavior, and typical coping patterns among three cohorts of university students before (2016), at the start of (2020), and after (2024) the pandemic, with 1016 students participating. Results: Perceived stress was significantly higher during the pandemic but returned to pre-COVID-19 levels afterward. Depression scores remained stable across cohorts. Burnout symptoms, particularly cynicism and academic efficacy, were significantly lower in the COVID-19 cohort. Study commitment, including subjective importance of studying, academic goals/ambition, willingness to exert oneself, and striving for perfection were lower during and after the pandemic than before. Emotional distancing peaked in 2020, suggesting disengagement as a coping strategy. Pre-COVID-19 students exhibited higher active coping scores than the COVID-19 and post-COVID-19 cohorts, while satisfaction with studies was highest post-pandemic, likely due to the return of in-person academic and social experiences. Conclusions: These findings reveal fluctuations in students’ stress, burnout, and study-related behavior over time. While stress-levels have normalized, study commitment and typical coping patterns such as active coping remain altered, indicating the pandemic’s lasting impact on students’ academic behavior and mental health.